CuZnInSe3‐based solar cells: Impact of copper concentration on vibrational and structural properties and device performance. (4th June 2019) - Guc, Maxim; Oliva, Florian; Kondrotas, Rokas; Alcobe, Xavier; Placidi, Marcel; Pistor, Paul; Saucedo, Edgardo; Perez‐Rodriguez, Alejandro; Izquierdo‐Roca, Victor
Abstract: CuZnInSe3 (CZISe) is an interesting alternative for the acknowledged Cu(In, Ga)Se2 absorber layer in thin film solar cells. While the partial replacement of scarce and expensive indium and gallium by zinc decreases manufacturing costs, the solid solution between CuInSe2 and ZnSe opens interesting options for band gap tuning and grading. Its potential as an absorber layer in photovoltaic devices has been demonstrated by obtaining 7.4 and 7.6 % efficiency in CZISSe‐ and CZISe‐based devices, respectively. On the other hand, the inherent complexity of the quaternary CZISe together with a lack of fundamental insights puts a limit to its current development. We present insights on the influence of the copper content ([Cu]/([Zn] + [In]) ratio) on the structural and optoelectronic properties of CZISe as well as the formation of secondary phases. By means of XRD and Raman scattering analyses, in addition to the sphalerite CZISe structure, a chalcopyrite Cu‐In‐Zn‐Se phase was found for high copper concentrations. On the contrary, for low Cu concentrations, unambiguous indications of a new ordered vacancy compound (OVC)–like phase formation both in XRD patterns and in Raman spectra were found. Conditions of pre‐resonant Raman scattering were applied to emphasize the new found phase and to estimate its concentration. Finally, the influence of each phase on the optoelectronic parameters and performance of solar cells with efficiencies of up to 7.4 % was studied. Abstract : CuZnInSe3 compounds were studied by means of XRD and Raman scattering analyses. For the high copper concentrations in addition to the sphalerite structure, a chalcopyrite phase was found, while for low Cu concentrations, unambiguous indications of a new ordered vacancy compound (OVC)–like phase formation were found both in XRD patterns and in Raman spectra. The influence of each phase on the optoelectronic parameters and performance of solar cells with efficiencies of up to 7.4% was studied.